2000
DOI: 10.1246/cl.2000.706
|View full text |Cite
|
Sign up to set email alerts
|

Per-C-6 Oligosaccharide-Branched Cyclodextrin Interacting with Both the Lectin and Drug

Abstract: The improved dual interactions with both the lectin (PNA, a cellular receptor model) and an anticancer drug (DXR) have been observed in per-C-6 oligosaccharide-branched cyclodextrin (2) using an optical biosensor based on SPR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…The authors hypothesized that the mono-Lac-aCD conjugate 79 should thread onto the polymer chain in aqueous solution and rest preferentially on the hydrophobic decamethylene segments (83), which was confirmed by 1 H NMR Scheme 33 Mal-aCD-PRX-coated polystyrene microspheres.…”
Section: -125mentioning
confidence: 95%
“…The authors hypothesized that the mono-Lac-aCD conjugate 79 should thread onto the polymer chain in aqueous solution and rest preferentially on the hydrophobic decamethylene segments (83), which was confirmed by 1 H NMR Scheme 33 Mal-aCD-PRX-coated polystyrene microspheres.…”
Section: -125mentioning
confidence: 95%
“…22) Figure 2 indicates the kinetic linear plots of 5 and 6. The association rate constant (k a ) and dissociation rate constant (k d ) of 5 (or 6) were 1.4ϫ10 4 Fig. 3.…”
Section: Resultsmentioning
confidence: 96%
“…These K a values are remarkably high when compared with the inclusion association of the lactose-b-CyD conjugate 4 4) or normal b-CyD which was on the order of 10 3 M…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Yasuda et al [14] have reported the synthesis of per-6galactosyl-glucono-amide-CD 12 and its monovalent analogue 13 (Fig. 3) by nucleophilic displacement of halogen-β-CD.…”
Section: Per-substituted Cyclodextrins On a Facementioning
confidence: 99%